Nikah Online Perspektif Kaedah Fiqh Al- Masyaqqah Tajlib At-Taisir - Syamsuddin Muir; Jumni Nelly; Rahman Rahman (Jurnal Keislaman, 2023)
Marriage is one of the most appropriate and honorable ways to continue offspring. Article 2 paragraph (1) of Law Number 1 of 1974 stipulates that marriage is valid if it is carried out according to the laws of each religion and belief. From the provisions of Article 2 paragraph (1) it is clear that those who are Muslim must heed the provisions and Islamic law in entering into marriage. Current technological developments are leading society towards the globalization of telecommunications, media and informatics. In the current condition, there are many problems that arise in a contract through electronic media, for example, online marriages where consent and consent transactions are carried out through connectivity or activities that are connected to a network or internet system (via online). Starting from the problems above, fiqh as a product of human thought related to Islamic law must be able to provide juridical answers to changes that occur in society. Therefore, opportunities for fiqh studies must always be open, and must be carried out by taking into account the social implications of the application of the products of legal thought, while maintaining their relevance to the will of the Qur'anic doctrines regarding human behavior.